2018
DOI: 10.18178/ijfe.4.2.93-100
|View full text |Cite
|
Sign up to set email alerts
|

The Drying of Foods and Its Effect on the Physical-Chemical, Sensorial and Nutritional Properties

Abstract: Drying of foods is an ancient practice that has been adopted to preserve foods beyond their natural shelf life. The process started with the exposure of foods to the sun, to extract from them a great proportion of the water, thus contributing for their conservation. The traditional solar dying with direct exposure to the sun had many disadvantages and presently more modern methods are used, such as hot air drying, spray drying, lyophilization, infrared, microwave or radiofrequency drying, osmotic dehydration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
89
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(98 citation statements)
references
References 24 publications
3
89
0
6
Order By: Relevance
“…Further studies of the weight differences due to products shrinkage and mass loss associated with oven drying condition are required. Microwave drying technique, in contrast, is an efficient method for moisture removal due to volumetric heating of food, which facilitates the transfer of moisture and prevents physical shrinkage and mass loss (Guiné, ; Lin, Durance, & Scaman, ; Rakesh & Datta, ). The results of this present study demonstrated that the drying duration required for microwave drying was shorter compared to the oven.…”
Section: Resultsmentioning
confidence: 99%
“…Further studies of the weight differences due to products shrinkage and mass loss associated with oven drying condition are required. Microwave drying technique, in contrast, is an efficient method for moisture removal due to volumetric heating of food, which facilitates the transfer of moisture and prevents physical shrinkage and mass loss (Guiné, ; Lin, Durance, & Scaman, ; Rakesh & Datta, ). The results of this present study demonstrated that the drying duration required for microwave drying was shorter compared to the oven.…”
Section: Resultsmentioning
confidence: 99%
“…Drying is a very complex process due to physical, chemical, and biochemical events that might occur during drying (Erbay, Koca, Kaymak-Ertekin, & Ucuncu, 2015). The drying process can affect the composition and properties of the food based on the drying method F I G U R E 1 Changes in moisture content depending on the drying temperature of control cheeses such as the degree of heat treatment or drying conditions (Guiné, 2018).…”
Section: Composition Of Cheesementioning
confidence: 99%
“…There are more drying methods applied in the food industry, for example, freeze‐drying, hot‐air drying, fluidized bed drying, spray drying, microwave‐assisted drying, osmotic dehydration, and combined drying consisted of two or more drying techniques. Some of them can be applied for drying of cheese (Guiné, ). Tray dryer is commonly used to dry the cheese under controlled condition.…”
Section: Introductionmentioning
confidence: 99%
“…However, the pre-treatment that being subjected to the oilseeds prior to the extraction process would probably possess impact towards the total yield of oil as well as its quality [24][25][26][27]. Food drying methods are the most ancient food preservation practice that still being widely utilized [28]. Nowadays, there are several methods have been employed to dry food, for instance, oven drying, cabinet drying, and freeze drying.…”
Section: Introductionmentioning
confidence: 99%